Efektivitas Pelayanan Publik Di Kantor Desa Pomolulu Kecamatan Balaesang Tanjung Kabupaten Donggala - Saripa; Natsir, Nawawi; Royfandi, Moh. (JPS: Journal of Publicness Studies, 2026)
The purpose of this study is to determine the effectiveness of public services at the Pomolulu Village Office, Balaesang Tanjung District, Donggala Regency. Using the theory of Sondang P. Siagian (2017:10) where there are 3 aspects, namely the Time Factor, the Accuracy Factor, and the Service Delivery Factor. The basis of the research uses a Qualitative Research Method, and the Type of Research is a descriptive approach. Using qualitative data analysis. Informants in this study numbered 5 people and data collection techniques were carried out through observation, interviews and documentation. Overall, the effectiveness of public services at the Pomolulu Village Office has been running quite well, especially in the aspects of accuracy and service style. However, the aspect of time discipline still needs attention so that the quality of public services can be more optimal. Overall, the effectiveness of public services at the Pomolulu Village Office has been running quite well, especially in the aspects of accuracy and service style. However, the aspect of time discipline still needs attention so that the quality of public services can be more optimal. The punctuality of the apparatus is still not optimal because there are still employees who arrive late and go home not according to the predetermined work schedule. Therefore, the work discipline of the apparatus still needs to be improved so that services can run optimally.